The genetic basis of plumage coloration and elevation adaptation in a clade of recently diverged alpine and arctic songbirds - Funk, Erik R; Spellman, Garth M; Winker, Kevin; Withrow, Jack J; Ruegg, Kristen C; Taylor, Scott A (Evolution, 2022)
Abstract Trait genetic architecture plays an important role in the probability that variation in that trait leads to divergence and speciation. In some cases, speciation may be driven by the generation of novel phenotypes through the recombination of genes associated with traits that are important for local adaptation or sexual selection. Here, we investigate the genetic basis of three plumage color traits, and one ecological trait, breeding elevation, in a recent avian radiation, the North American rosy-finches (Leucosticte spp.). We identify unique genomic regions associated with each trait and highlight 11 candidate genes. Among these are well-characterized melanogenesis genes, including Mitf and Tyrp1, and previously reported hypoxia-related genes including Egln1. Additionally, we use mitochondrial data to date the divergence of rosy-finch clades which appear to have diverged within the past 250 ky. Given the low levels of genome-wide differentiation among rosy-finch taxa, and evidence for extensive introgression in North America, plumage coloration and adaptation to high elevations have likely played large roles in generating the observed patterns of lineage divergence. The relative independence of these candidate regions across the genome suggests that recombination might have led to multiple phenotypes, and subsequent rosy-finch speciation, over short periods of time.